English Foreign Language Students’ Strategies in Overcoming Speaking Problems - Ari Prasetyaningrum; Laila Wati; Zahratul Fikni (VELES Voices of English Language Education Society, 2020)
This study aimed at knowing studentsâ€™ dominant problems in speaking and studentsâ€™ strategies in overcoming their speaking problems. In this study the researcher used qualitative research. The subject of this study was the studentsâ€™ of the second semester of physics education study program  at Hamzanwadi University which consisted of 12 studentsâ€™. Observation, interview and questionnaire were used for collecting data. The result of this study showed that studentsâ€™ got the problems in speaking, the studentsâ€™ dominant problems those were anxiety of speaking, unavailability environment and lack of vocabularies. In solving the studentsâ€™ problem in speaking, the studentsâ€™ used some strategies those were role-play, telling-story and games.